PENGEMBANGAN STANDAR OPERASIONAL PROSEDUR PADA PROSES MANAJEMEN PEMELIHARAAN DAN PERAWATAN BANGUNAN HIGH RISE BUILDING (STUDI KASUS GEDUNG MIXED USE PRAXIS SURABAYA) (Magister Teknik Sipil, Fakultas Teknik, Universitas 17 Agustus 1945 Surabaya, 2021)
Building is a physical form of construction work that is integrated with its domicile, partially or wholly located above and/or in the ground and/or water. The building functions as a place for humans to carry out their activities, both for housing or residence, religious activities, business activities, social activities, culture, and special activities. In the process of building maintenance and maintenance management, standard operating procedures are needed to maintain and maintain the reliability of the building. In this case, the role of the building manager or property management is very important in carrying out maintenance and care standards in a building. In the research that has been carried out, there are several deviations in the maintenance and maintenance activities of buildings managed by property management X, building Y, among others in terms of organization, maintenance planning and information and system maintenance. The development of standard operating procedures with the preparation of 13 procedures in building maintenance and maintenance activities is expected to support the running of SOPs in property management X building Y. The estimated operational and maintenance costs for buildings are planned based on the calculation of a single interest rate with the value of bank interest inflation per year. The estimated cost in the first year, which is 2021, the estimated operational and maintenance costs are Rp. 11,468,690,944.17 with an estimated increase in interest rates of 10% per year for the following years. With the development of standard operating procedures in the process of building maintenance and maintenance, it is hoped that the building management can work well in maintaining the reliability of the building.